Pengaruh Perlakuan Alkali terhadap Sifat Tarik Bahan Komposit Serat Rami-Polyester - Kuncoro Diharjo (Jurnal Teknik Mesin (Sinta 3), 2006)
The Natural Composite (NACO) is material that has a good potential to be developed in Indonesia. The mechanical bonding of the composite reinforced natural fiber can be increased by using chemical treatment of fiber or by using the addition of coupling agent. The chemical treatment, for example alkali treatment, is often used because it is more economic. The objective of this research is to investigate the effect of alkali treatment to the tensile properties of unidirectional continuous ramie fiber reinforced polyester composite. Visual inspections were performed to asses the mechanism of fracture. The ramie fiber was immersed in the alkali solution (5% NaOH for 0, 2, 4, and 6 hours. And then, it was washed using fresh water and dried naturally. The matrix used in this research is unsaturated polyester resin 157 BQTN with MEKPO hardener 1% (v/v). The composites were made by using press mold method for Vf " 35%. All specimens were post cured at 62 0C for 4 hours. The tensile test specimens were produced according to ASTM D-638. The tensile test was carried out on a tensile testing machine and the elongation was measured using an extensometer. The fracture surface was investigated to identify the mechanism of fracture. The result shows that the tensile strength and strain of the composites have the optimum values for 2 hours treated fiber, i.e. 190.27MPa, and 0.44% respectively. The longer time of the alkali treatment of fiber increases its modulus. The composite prepared by 6 hours treated fiber has the lowest strength. The fracture surfaces of the composites prepared by 0, 2, and 4 hours alkali treated type are classified as splitting in multiple area. In contrast, the fracture of the composite prepared by 6 hours treated fiber has sigle fracture type. The fracture surface of the composite reinforced untreated fiber shows fiber pull out. Abstract in Bahasa Indonesia : Komposit alam (NACO) adalah material yang memiliki potensi yang baik untuk dikembangkan di Indonesia. Mechanical bonding komposit yang diperkuat serat alam dapat ditingkatkan dengan perlakuan kimia serat atau mengunakan coupling agent. Perlakuan kimia, seperti perlakuan alkali, sering digunakan karena lebih ekonomis. Tujuan penelitian ini adalah menyelidiki pengaruh perlakuan alkali terhadap sifat tarik komposit berpenguat serat rami kontinyu dengan matrik poliester. Pengamatan visual dilakukan untuk menyelidiki mekanisme perpatahan. Serat rami direndam di dalam larutan alkali (5% NaOH) selama 0, 2, 4, dan 6 jam. Selanjutnya, serat tersebut dicuci menggunakan air bersih dan dikeringkan secara alami. Matrik yang digunakan dalam penelitian ini adalah resin unsaturated polyester 157 BQTN dengan hardener MEKPO 1% (v/v). Komposit dibuat dengan metode cetak tekan pada Vf " 35%. Semua spesimen dilakukan post cure pada suhu 62 0C selama 4 jam. Spesimen uji tarik dibuat mengacu pada standar ASTM D-638. Pengujian tarik dilakukan dengan mesin uji tarik dan perpanjangan diukur dengan menggunakan extensometer. Penampang patahan diselidiki untuk mengidentifikasi mekanisme perpatahannya. Hasil penelitian menunjukkan bahwa kekuatan dan regangan tarik komposit memiliki harga optimum untuk perlakuan serat 2 jam, yaitu 190.27 Mpa dan 0.44%. Komposit yang diperkuat serat yang dikenai perlakuan 6 jam memiliki kekuatan terendah. Penampang patahan komposit yang diperkuat serat perlakuan 0, 2, dan 4 jam diklasifikasikan sebagai jenis patah slitting in multiple area. Sebaliknya, penampang patahan komposit yang diperkuat serat perlakuan 6 jam memiliki jenis patah tunggal. Penampang patahan komposit yang diperkuat serat tanpa perlakuan menunjukkan adanya fiber pull out. Kata kunci: Perlakuan alkali, serat rami, unsaturated polyester, sifat tarik.